Analisis Hukum Pidana Islam terhadap Putusan Nomor 189/PID.SUS/2024/PN PDG tentang Tindak Pidana Pemilu - Reza Topik Anugrah; Beni Firdaus (Lembaga Yasin AlSys, 2026)
Campaign violations in official government activities constitute an important issue in electoral law because they have the potential to undermine the principles of fairness and the neutrality of public space. This study was motivated by the case of a campaign violation committed by Dean Asli Chaidir during an official MSME forum activity in Padang City, which was suspected of violating electoral provisions through an appeal to vote at a government facility. This study aims to analyze the judge’s considerations in Decision Number 189/Pid.Sus/2024/PN PDG and to assess their conformity from the perspective of Islamic criminal law. This study employed library research with a qualitative approach. The data were derived from the Qur’an, electoral laws and regulations, and court decisions, collected through document study and interviews, and then analyzed descriptively and qualitatively. The results show that the defendant was proven to have committed a campaign violation in a government building without official permission, even though he was present as an invitee. The judge found elements of an appeal to vote and political promises as forms of violation, but imposed a suspended sentence and a fine by considering humanitarian aspects. From the perspective of Islamic criminal law, the act falls within the category of jarimah ta’zir, which is oriented toward public benefit, deterrence, and the reform of the offender. These findings contribute to strengthening the study of electoral criminal law and Islamic criminal law, and affirm that law enforcement against campaign violations in government facilities must take into account the aspects of justice, benefit, and the objectives of punishment.